Pendidikan Anti Korupsi Dalam Pendidikan Agama Islam - Imelda, Ade (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2017)
Anti-corruption education must be introduced from children to learn about life, meaning that since the beginning the child is introduced to anti-corruption values. Planting carried out consistently and continuously, will foster a child's personality attitude. Basically a person's personality does not appear instantly but through a process. Anti-corruption education can be implemented both formally and informally. At the formal level, elements of anti-corruption education can be included in the curriculum inserted / integrated into the subject. The concept of anti-corruption by getting used to living anti-corruption, through the introduction of an anti-corruption lifestyle, due to corruption, and the planting of religious teaching values into students. The implications of anti-corruption education in Islamic religious education, namely the curriculum must link all subjects to anti-corruption values, learning with habituation and exemplary and teachers must be able to be role models, provide information about the dangers of corruption, and familiarize students with anti-corruption.